Optimalisasi Marketing Channel U-Fat dan Pemberdayaan Perempuan Pada Fatayat NU Kecamatan Sirampog Brebes - Pribadi, Prayoga; Suyanto, M. Daffa Izulhaq; Chandra, Syahrul Aditya (Universitas Pahlawan Tuanku Tambusai, 2024)
The growth of internet users in Indonesia has increased significantly from year to year, reaching more than 175.4 million users in January 2020, which is dominated by internet users via mobile devices rather than desktop PCs, namely 124% of the Indonesian population. Therefore, it is urgent for every company to integrate digital marketing into all levels of society. Fatayat NU is an organization for women which was formed and is under the auspices of Nahdlatul Ulama. Friends of Fatayat NU Sirampog sub-district has members, around 70% of whom own businesses. However, it cannot be managed optimally, especially in the use of technology by utilizing digital marketing. Therefore, assistance is needed in marketing products digitally by utilizing information technology so that people can further optimize the marketing methods that will be used. The aim of this PKM activity is to improve the economy and empower women by optimizing smartphones through optimizing omni channel marketing. The results of this activity increase participants' knowledge about digital marketing methods, so that they can improve the economy.